2015
DOI: 10.1186/s12872-015-0049-6
|View full text |Cite
|
Sign up to set email alerts
|

Chest pain in the emergency department: risk stratification with Manchester triage system and HEART score

Abstract: BackgroundFast and accurate chest pain risk stratification in the emergency department (ED) is critical. The HEART score predicts the short-term incidence of major adverse cardiac events (MACE) in this population, dividing it in three risk categories. We aimed to describe the population with chest pain, to characterize the subgroup of patients with acute coronary syndrome (ACS) and to assess the prognostic value of Manchester triage system and of HEART score.MethodsRetrospective observational study including p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
5
34

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(93 citation statements)
references
References 16 publications
4
50
5
34
Order By: Relevance
“…In the study of Leite et al (5), additional diseases such as hypertension (in 50.7%), diabetes (in 11.8%), coronary artery disease (in 12.7%), atrial fibrillation (in 18.5%), heart failure (in 16.6%) and chronic pulmonary obstructive disease (in 7.6%) were present. In their study, Coşkun et al (7) found comorbid diabetes mellitus, coronary artery disease and hyperlipidemia in 13.6%, 26.8% and 4.1% of the patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Leite et al (5), additional diseases such as hypertension (in 50.7%), diabetes (in 11.8%), coronary artery disease (in 12.7%), atrial fibrillation (in 18.5%), heart failure (in 16.6%) and chronic pulmonary obstructive disease (in 7.6%) were present. In their study, Coşkun et al (7) found comorbid diabetes mellitus, coronary artery disease and hyperlipidemia in 13.6%, 26.8% and 4.1% of the patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the mean ages were 56.9±19, 41.35±12.20 and 59.6±13.7 years (1,5,6). In these studies, 52.6%, 58.4% and 44.8% of the patients were male, respectively (1,6,7).…”
Section: Discussionmentioning
confidence: 99%
“…By appreciating each of these five elements with 0, 1 or 2 each patient will receive a score of 0-10. The HEART score divides patients into low (0-3), intermediate (4)(5)(6) or high-risk groups (7-10), with mean risks of an event of 0.9, 12 and 65%, respectively. One limit of the TIMI and GRACE scores is that they have been originally developed for patients with confirmed ACS in the setting of coronary unit.…”
Section: Discussionmentioning
confidence: 99%
“…Na primeira sessão foram apresentados os resultados da revisão sistemática e na segunda sessão foram apresentados os resultados do estudo primário conduzido no HU-USP. (50) ED (Hospital de nível terciário)…”
Section: Resultsunclassified
“…Como já mencionado, somente dois estudos (33,50) (28,49,51) , enquanto apenas um deles apresentou um limite superior do IC valor maior que 0,90 (50) . Entretanto, este estudo apresentou um intervalo de confiança bastante amplo, reduzindo seu peso dentro da revisão sistemática.…”
Section: Análise E Síntese Dos Dadosunclassified